JIRA development cookbook : your one-stop resource for mastering extensions and customizations in JIRA 7+ - Kuruvilla, Jobin (Packt Publishing, 2016)
Your one-stop resource for mastering extensions and customizations in JIRA 7+ About This Book Explore the new features of JIRA 7 and best practices for agile development and integration with development tools Customize the look and feel of your JIRA UI to match your specific user needs Create seamless reports that make sense of your data through easy-to-use techniques Who This Book Is For If you are a JIRA developer or administrator, or a project manager who wants to fully exploit the exciting capabilities of JIRA, then this is the perfect book for you. What You Will Learn Create and deploy your own JIRA plugins Manipulate workflows to transform JIRA into a user-friendly system Create custom reports that show statistics for particular people, projects, versions, or other fields within issues Simplify reporting by writing your own JIRA gadgets, which can be added into a user's dashboard Master database handling by extending and retrieving custom field details from the database Deal with custom fields on an issue and program custom field option In Detail JIRA provides issue and project tracking for software development teams to improve code quality and the speed of development. With the new version of JIRA, you can create your own JIRA plugins and customize the look and feel of your JIRA UI easier than ever. JIRA Development Cookbook , Third Edition, is a one-stop resource to master extensions and customizations in JIRA. This book starts with recipes about simplifying the plugin development process followed by recipes dedicated to the plugin framework. Then, you will move on to writing custom field plugins to create new field types or custom searchers. You will also learn how to program and customize workflows to transform JIRA into a user-friendly system. With so much data spanning different projects, issues, and so on, we will cover how to work on reports and gadgets to get customized data according to our needs. At the end of the book, you will learn how to customize JIRA by adding new tabs, menus, and web items; communicate with JIRA via the REST APIs; and work with the JIRA database. Style and approach JIRA Development Cookbook , Third Edition, is a one-stop resource to master extensions and customizations in JIRA. This book starts with recipes about simplifying the plugin development process followed by recipes dedicated to the plugin framework. Then, you will move on to writing custom field plugins to create new field types or custom sear...
Includes index.
Keywords: JIRA (Computer file); Java (Computer program language); Application software -- Development.; Java (Langage de programmation); Logiciels d'application -- Développement.; BUSINESS & ECONOMICS -- Advertising & Promotion.; Application software -- Development